Computer-Supported Collaborative Learning Using POGIL Methodology: An Exploration - Dixon, John (2018)
The aim of this research is to explore the possibilities of implementing Process Orientated Guided Inquiry Learning (POGIL) in an online environment. It is framed by previous research into Computer-Supported Collaborative Learning (CSCL). A POGIL activity was modified for completion online by three small groups of grade 10 chemistry students. The students collaborated through three online communication tools, Google Docs, Google Hangouts and Google Classroom. As a comparison, three small groups from another class completed a regular face-to-face POGIL activity. The study took place through action research, in which challenges to online implementation of POGIL were identified and a suitable activity was designed to address them. The challenges included supporting high quality interactions, maintaining the role of the instructor as a facilitator and challenging students to demonstrate life-long learning process skills. From these challenges three specific research questions were identified. Quantitative and qualitative data revealed the participation and interaction patterns of the students, the effect of teaching presence on the participation and the extent of the critical thinking in the online groups. Participation within groups was uneven, and not all groups fully utilised all of the communication tools. Analysis of discussion threads showed that the instructor changed the nature of the participation in the online activity, increasing dialogue and drawing students into whole class discussion. There was evidence of critical thinking in students’ approach to the activity, but the extent varied across the three Google apps.